2001
DOI: 10.1159/000047689
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ischemia and Embolism

Abstract: Objectives: To identify the most likely mechanisms of retinal ischemia and embolism in a hospital-referred population, and to determine the frequency of recurrent vascular events during the 3-month period following initial presentation. Methods: Consecutive patients presenting to 2 tertiary medical centers and their outpatient clinics were prospectively enrolled over a 22-month period. Eligible patients presented with histories of transient or permanent monocular visual loss, or had evidence of asymptomatic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Previous studies have reported that the incidence of experiencing a subsequent stroke was highest in the first month after retinal ischemia. [7, 11, 12, 16] Considering these findings, early treatment and appropriate interventions, such as carotid endarterectomy or carotid stenting, may be carefully considered for the prevention of a second vascular event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that the incidence of experiencing a subsequent stroke was highest in the first month after retinal ischemia. [7, 11, 12, 16] Considering these findings, early treatment and appropriate interventions, such as carotid endarterectomy or carotid stenting, may be carefully considered for the prevention of a second vascular event.…”
Section: Discussionmentioning
confidence: 99%
“…Babikian et al reported that the most common identifiable etiology (22.1%) of RAO in American subjects was stenosis of the extracranial carotid artery and OA stenosis was reported in only 2.6%. [11] However, Asians have a higher incidence of intracranial atherosclerosis than Caucasians. Anatomically, the retinal artery arises from the OA, the first intracranial branch of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cardiac lesions appear to be the second cause of importance [5]. When cardio-embolic origin of stroke is suspected, achieving the appropriate screening is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by Kaja et al, this model is able to recapitulate the cellular and molecular changes in the retina after stroke. This is particularly clinically relevant since acute thrombotic/embolic stroke and transient ischemic attack in humans are often associated with temporary diminishment (ie, amaurosis fugax) or even permanent loss of vision [26].…”
Section: Discussionmentioning
confidence: 99%